Electrophysiological Studies on The Dynamics of Luminance Adaptation in the Mouse Retina - Joachimsthaler, Anneka (Vision (Basel), 2017)
To date, most studies involving in vivo electroretinography in mice are performed on steady state adapted animals. In this study, we focused on the dynamics of adaptation to high and low light levels in the mouse retina. Two flash electroretinogram (ERG) protocols and one flicker ERG protocol were employed. In the two flash ERG protocols, the animals were adapted to either 25 or 40 cd/m(2) white light and ERGs were recorded for up to 15 min of adaptation. Afterwards, flash ERGs were recorded for up to 45 min of dark adaptation. Amplitudes of the flash ERG increased during light adaptation, while implicit times of the different wave components decreased. During subsequent dark adaptation, the amplitudes further increased. The increase in a-to-b-wave ratio indicated adaptational processes at the photoreceptor synapse. In the flicker ERG protocol, the responses to 12 Hz sinusoidal luminance modulation during the adaptation to 25 cd/m(2) and a 1 cd/m(2) mean luminances were recorded. The amplitudes of the first harmonic components in the flicker protocol decreased during light adaptation but increased during dark adaptation. This is at odds with the changes in the flash ERG, indicating that adaptation may be different in different retinal pathways.